Simulasi Daun Kemudi Kapal Dengan Variasi Beban - Rakhman, Arif Rakhman Suharso; Ario Hedartono; Susanto (Universitas Muhammadiyah Metro, 2024)
A ship's steering system contains steering gear auxiliary machinery which functions to move the rudder or rudder when maneuvering the ship where the ship's rudder is located at the stern of the ship behind the propeller. This research aims to test the MG995 servo which is used to move a simulated ship's rudder to measure the time and accuracy of the angle of rotation of the rudder with various load variations in accordance with Solas rules. This research is a continuation of the previous research roadmap regarding sensor comparison for ship steering simulations. The capabilities of the MG995 servo were tested by comparing several loads to test stall torque conditions and the ability to move the ship's rudder. The equipment used in preparing this ship steering simulation includes a rudder to determine the position towards the port side and starboard side, an Arduino as control equipment, a rotary encoder to determine the rudder angle, a servo to move the rudder, and a rudder to test the load on the servo.